2015
DOI: 10.1080/02640414.2015.1025235
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium phosphate and caffeine loading on repeated-sprint ability

Abstract: The effects of sodium phosphate and caffeine supplementation were assessed on repeated-sprint ability. Using a randomised, double-blind, Latin-square design, 12 female, team-sport players participated in four trials: (1) sodium phosphate and caffeine, (2) sodium phosphate and placebo (for caffeine), (3) caffeine and placebo (for sodium phosphate) and (4) placebo (for sodium phosphate and caffeine), with ~21 days separating each trial. After each trial, participants performed a simulated team-game circuit (4 × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 23 publications
2
30
1
1
Order By: Relevance
“…The caffeine stands out as the most ergogenic substance to be taken before practicing anaerobic exercises (high intensity and short duration), because it staves off fatigue and, thus, improves performance (Buck et al, 2015). However, the present study did not find physical performance improvement in CG in comparison to PG differently from other studies (Chen et al, 2015; Del Coso et al, 2016).…”
Section: Discussioncontrasting
confidence: 87%
“…The caffeine stands out as the most ergogenic substance to be taken before practicing anaerobic exercises (high intensity and short duration), because it staves off fatigue and, thus, improves performance (Buck et al, 2015). However, the present study did not find physical performance improvement in CG in comparison to PG differently from other studies (Chen et al, 2015; Del Coso et al, 2016).…”
Section: Discussioncontrasting
confidence: 87%
“…While the former may simply be a quirk of the statistical analysis in a small sample size, there may be some interaction that requires further investigation. Similar findings regarding the combination of caffeine and phosphate [42, 43] also merit additional research.…”
Section: Additive and Interactive Effects Of The Use Of Combinations supporting
confidence: 57%
“…Effects of phosphate seen when fresh as well as fatiguedCaffeine and phosphate Kopec et al [42]Trained team sport athletes ( n  = 11 M)Crossover design to produce caffeine, phosphate, combined, and placebo trials6 mg/kg caffeine @ 60 min pre-exercise and/or 6 days @ 50 mg/kg/dayFFM sodium phosphate in split dosesWashout of 17 days between trialsTeam sport 6 × 20 s sprints Undertaken @ 0, 30, and 60 around a 2 × 30 min simulated team game circuitCaffeine: NoPhosphate: PerhapsInteraction: independent mechanism with possibly counteractive effectAlthough results failed to reach statistical significance, effect size and magnitude based analysis revealed that, compared with placebo, phosphate resulted in the fastest times for all sprints with moderate-large effect sizes and “likely” to “very likely” benefits. The beneficial effects of combined were smaller, and the effects of caffeine alone were minimal Buck et al [43]Recreationally trained team sport athletes ( n  = 12 F)Crossover design to produce caffeine), phosphate, combined, and placebo trials6 mg/kg caffeine @ 60 min pre-exerciseand/or 6 days @ 50 mg/kg/day FFM sodium phosphate in split dosesWashout of 17 days between trialsTeam sport 6 × 20 s sprints Undertaken @ 0, 30, and 60 around a 4 × 15 min simulated team game circuitCaffeine: NoPhosphate: YesInteraction: independent mechanism with no additive effectOverall results showed that combined and phosphate alone improved sprint times when fresh (set 1) and fatiguing (set 2 and 3) compared with placebo. Caffeine alone had small effects

BJ beetroot juice, BM body mass, ES effect size, FFM fat free mass, GI gastrointestinal, JSPT judo specific performance test, M male, F female, TT time trial

a Randomized, double-blind, placebo-controlled unless noted

…”
Section: Additive and Interactive Effects Of The Use Of Combinations mentioning
confidence: 99%
“…Sodium phosphate (SP) is a legal nutritional supplement that has been suggested to improve athletic performance (Currell et al, 2012). Several mechanisms have been proposed to explain this potential ergogenic effect, including an increase in resting erythrocyte 2, 3-diphosphoglycerate (2, 3-DPG) concentration (promoting oxygen offloading at the muscle via a reduction in oxyhaemoglobin affinity) (Bremner et al, 2002;Cade et al, 1984), an enhancement of myocardial contractility (Kreider et al, 1992), an increase in extracellular hydrogen phosphate (HPO4 -) concentration (facilitating hydrogen ion buffering) (Buck et al, 2015;Kopec et al, 2016), and an increase in the activity of various oxidative enzymes, such as phosphofructokinase and glyceraldehyde 3-phosphate dehydrogenase (Buck et al, 2013).…”
Section: Introductionmentioning
confidence: 99%